PENGEMBANGAN BAHAN AJAR TAJWID DI SMP TAHFIDZ AL-AMIEN - Abdul Hamid Bakir (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2018)
Subject Tajweed is the basic science to learn how to read the Qur'an in both good and true, is also a prerequisite for junior high students Tahfidz Al-Amien before starting the program memorize the Quran. Realization of these goals require recitation of subjects learning resources that support the learning process. Based on the results of preliminary studies in the field through observation and interviews found that the majority of junior high school students in grade VII Tahfidz Al-Amien had difficulty in learning Tajweed with a variety of different reasons including: the difficulty distinguishing between a legal reading by reading other law, the difficulty in pronunciation hijaiyah letter and the application of the rules of tajweed in reading the Qur'an, and the lack of teaching materials used in the presentation of examples, explanations, and practice questions. Another problem lies in the learning process is emphasized only on the ability of students to memorize rules and examples without being to understand the concept of the examples and rules. So what happened next is when the learning activities students completed only good in theory but weak in application. One alternative to solve these problems is to design and develop instructional materials. The research objective of this development was to produce a package of teaching materials tajwid subjects designed and developed according to the characteristics and learning needs of junior high school students in grade VII Tahfidz Al-Amien. The model used in developing these materials is Dick Carey model. The reason for Dick Carey model is based on the premise that this model: 1) use a systems approach to complete the steps. 2) has four characteristics that should be owned in the development of learning, namely: refers to the goal, there is harmony with the objective, systematic, and based on the evaluation.